Society News (Res Medica, 2014)
The two most significant recent events in the life of the Society were undoubtedly the Symposium on “Immunological Aspects of Cancer” held in the Autumn of 1970 and the visit by Dr. Issels from the Ringberg Klinik in the early Spring of 1971 .The Symposium, which was conceived, nurtured and presented by Ian Smith, then Senior President, attracted a great deal of attention in the Medical Press — especially in the British Medical Journal which covered the event in two consecutive issues of the magazine.  The Symposium was held in the George Square Lecture Theatre and the main participants were, “in order of appearance”, Professor Klein, Dr. Allison, Professor Doll, Dr. Kinlen, Dr. Stuart, Dr. Burkitt, Dr. Bagshawe, Dr. Hamilton Fairley, Professor Alexander, Professor Sir Michael Woodruff, Professor Mathe, Professor Crile and, of course, as general coordinator, Ian Smith.The list is impressive and yet equally distinguished assemblies occur frequently in the many “Congress Spots” of the world.  Why did the R .M.S. Symposium have such a special appeal?